2010
DOI: 10.1308/003588410x12518836440522
|View full text |Cite
|
Sign up to set email alerts
|

Critical appraisal of subjective outcome measures used in the assessment of shoulder disability

Abstract: INTRODUCTION: Objective measures can be impractical in some settings, because they are time consuming and require face-toface contact. More recently, there is an increasing trend towards the use of subjective outcome measures. Hence, in this article, five common subjective shoulder outcome measures are critically appraised in terms of their development, validity, reliability, responsiveness and clinical application. MATERIALS AND METHODS: Following an extensive literature search, five common shoulder patient-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 14 publications
0
46
0
Order By: Relevance
“…Some of the most commonly used questionnaires identified in the literature are the Oxford Shoulder Score; Disabilities of the Arm, Shoulder, and Hand; and Shoulder Pain and Disability Index. 37 These questionnaires provide clinicians with subjective outcome measures that allow them to evaluate the symptomatic relief and results of treatment as athletes recover from acute injury. These questionnaires are convenient to use, but they are not applicable to all shoulder injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the most commonly used questionnaires identified in the literature are the Oxford Shoulder Score; Disabilities of the Arm, Shoulder, and Hand; and Shoulder Pain and Disability Index. 37 These questionnaires provide clinicians with subjective outcome measures that allow them to evaluate the symptomatic relief and results of treatment as athletes recover from acute injury. These questionnaires are convenient to use, but they are not applicable to all shoulder injuries.…”
Section: Discussionmentioning
confidence: 99%
“…These questionnaires are convenient to use, but they are not applicable to all shoulder injuries. 37 In addition, because the questionnaire answers are subjective, clinicians may not always be willing to rely solely on their athletes' self-reports. Therefore, we need to evaluate more objective outcome measures to better understand the progressive recovery process that occurs after an acute shoulder injury.…”
Section: Discussionmentioning
confidence: 99%
“…It has good correlation with clinical findings. Again the OSS does not assess shoulder instability [21] and, as a consequence the oxford instability score (OSIS) has been developed subsequently [22] (see below). Olley et al [20] concluded that the OSS can be used for audit purposes, however, they have suggested that larger prospective studies should be carried out to identify whether OSS varies with age, gender, and size of rotator cuff tear or not.…”
Section: Oxford Shoulder Scorementioning
confidence: 99%
“…Answers are tallied to produce a summary score, which is intended to represent the impact of shoulder pain and dysfunction on an individual's health-related quality of life, with respect to activity limitations and participation restrictions. Studies [7][8][9][10] comparing the performance of commonly used shoulder or upper extremity region-specific PROs have identified at least five measures [Disabilities of the Arm, Shoulder and Hand questionnaire (DASH), Oxford Shoulder Score (OSS), Shoulder Pain and Disability Index (SPADI), American Shoulder and Elbow Surgeons standardized assessment form (ASES), and Simple Shoulder Test] with accumulating evidence for the psychometric properties of validity, reliability, responsiveness and practicality across a range of shoulder conditions. The evidence suggests these PROs have psychometrics that are sufficient to evaluate the health status at a single point in time and assess change over time to determine treatment effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence suggests these PROs have psychometrics that are sufficient to evaluate the health status at a single point in time and assess change over time to determine treatment effectiveness. [7][8][9][10] There are a large number of psychometrically assessed and validated shoulder-specific, upper extremity region-specific and shoulder disease-specific PROs. This presents a challenge in the evidence-based selection of PROs.…”
Section: Introductionmentioning
confidence: 99%